The Story of a Commercial Street: Growth, Decline, and Gentrification on Gottingen Street, Halifax - Roth, Nathan; Grant, Jill (Urban History Review / Revue d'histoire urbaine)

(untitled) (Urban History Review / Revue d'histoire urbaine, 2015)
Between the 1830s and 2010s Gottingen Street in Halifax, Canada, transitioned from a residential street, to a commercial corridor, to an area of community services, to a revitalizing “hip” area. Its story reflects the influence of changing regulatory regimes, transportation modes, commercial practices, and cultural values. The article follows uses in selected properties on the street to tell the story of an area shifting in use and character as a result of major infrastructure investments and changing economic conditions between 1910 and 2015.